Peningkatan Kemampuan Motorik Halus Anak Kelompok A Melalui Kegiatan Finger Painting - Vivi Irzalinda; Gian Fitria Anggraini; Nopiana Nopiana (FKIP UNSULTRA, 2026)
This study employed a Classroom Action Research (CAR) design aimed at improving the fine motor skills of Group A children through finger painting activities at KB Al Haqiqi in 2025. The study was motivated by the importance of fine motor development as a foundation for children's learning skills and academic readiness in early childhood education. The participants consisted of 10 children from Group A. The research was conducted in two cycles, each involving four stages: planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation. The findings revealed that finger painting activities effectively improved the children's fine motor skills. At the end of the second cycle, 80% of the children demonstrated better hand and finger coordination, 70% were able to complete art tasks such as creating patterns and filling picture areas more accurately, and 60% showed increased self-confidence in expressing their ideas through artistic activities. Therefore, it can be concluded that finger painting is an effective learning activity for enhancing the fine motor skills of Group A children at KB Al Haqiqi. Furthermore, finger painting can be implemented as an enjoyable, meaningful, and developmentally appropriate learning strategy in early childhood education settings.